FORMATION OF THE VALUABLE ORIENTATION IN THE SYSTEM OF ECONOMIC TRAINING OF THE FUTURE SPECIALISTS IN THE SPHERE OF COOPERATION - Stebljuk, Svitlana V. (Educological discourse, 2016)
This article deals with the notion of «valuable cooperation» and their importance in developing of the personality. There are characterized modern methods of forming valuable orientations in the system of economic training of the future specialists in the sphere of cooperation. The author dwells upon traditional and up-to-date bringing up methods that are effective in the teaching process in the sphere of cooperation. It proposed separate educational forms with the students and also recommended the plan of their realization.